The Janus of Yeŋiçeri: Analysis of The Ambivalence of Turkey's Foreign Policy Toward Israel - Yusuf Pribadi; Reni Windiani; Marten Hanura; Muhammad Adnan (Journal of Islamic World and Politics, 2024)
This article aims to explain the ambivalence of Turkey's foreign policy towards Israel during President Erdoğan's leadership in 2014 – 2018. The problem that arises is: Why does Turkey implement a foreign policy that is ambivalent towards Israel? This article uses the theoretical basis of neoclassical realism and groupthink to solve the problem. The method used in this research is explanatory-qualitative with interviews. The findings in this research showed that the ambivalence in Turkish foreign policy towards Israel during President Erdoğan's leadership (2014 – 2018) was influenced by aspects of systemic international politics and local political dynamics as well as Neo-Ottoman views in the formulation of their national interests.